Pengaruh Pelaksanaan Tugas Kepala Madrasah Terhadap Profesionalitas Guru di MTs Negeri Model Kota Sorong - Alfan Rahman; Agus Yudiawan (IAIN Sorong, 2018)
In developing a madrasa, it requires a leader or madrasa head who is capable and has leadership skills. the quality of madrasas is determined by the quality of madrasa head leadership. The madrasa head can successfully lead the madrasa if he understands the existence of a madrasa as a complex and unique organization, and is able to carry out his role as a leader, manager, administrator and supervisor. In order to carry out their duties properly, a madrasa head needs to have professional subordinates, in this case, the teacher. Every step of a teacher in dealing with every task and responsibility entrusted to him needs to be carried out as well as possible. This is the meaning of professionalism itself. The purpose of this research is to prove the influence between the implementation of the duties of the madrasah headteacher professionalism. This study uses a quantitative approach to the type of descriptive research and data analysis using the SPSS 16 For Windows program. The population in this study were all teachers in Sorong City Model MTs, totaling 43 people as respondents. The results of the data analysis showed that there was an influence between the implementation of the duties of the madrasah headmaster on the professionalism of teachers in the Sorong City Model MTs, which only affected 10.5%, the rest of which was 89.5% influenced by other factors.